1968
DOI: 10.3758/bf03210437
|View full text |Cite
|
Sign up to set email alerts
|

Integration of information in a visual discrimination task

Abstract: 2The integration of information model ofsignal detection theory (SDT) was tested in a multiple observation tilt-discrimination task. Improvement in discriminability with additional observations was consonant with theory over two observations, but observations beyond the second yielded less improvement than predicted by the integration model. Analyses of operating characteristics lent some support to the applicability of SDr to the tilt-discrimination task.This paper describes two experiments designed to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1970
1970
1998
1998

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…As an example, the model is applied to the results of a study performed by Ulehla, Halpern, and Cerf (1968). These researchers conducted an experiment requiring subjects to identify the direction of tilt of a line (either left or right).…”
Section: Stimulus Integration Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…As an example, the model is applied to the results of a study performed by Ulehla, Halpern, and Cerf (1968). These researchers conducted an experiment requiring subjects to identify the direction of tilt of a line (either left or right).…”
Section: Stimulus Integration Modelmentioning
confidence: 99%
“…In Figure 3, diamonds are plotted to represent values of(lld')2 computed from the d' values presented in Experiment 2 of Ulehla et al (1968).7 These values are plotted as a function of IIN, where N is the number of stimulus observations on which each d' value is based. As is evident from the figure, the data are extremely well described by a straight line function (r = .997) with a slope7 of 1.28 and an intercept of .09.…”
Section: Stimulus Integration Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of multiple responses and certainty estimates was evaluated using the index of signal detectability (d'), Within TSD, d' is a basic measure of the discriminability of a pair of alternative stimuli for a given S and is theorized to be independent of response bias. A more complete explanation of d' (and the , , Ulehla et al (1968). Empirical d' values were obtained for each S by referring his hit rates and error rates to tables of d' (Elliott, 1964).…”
Section: Resultsmentioning
confidence: 99%
“…In two separate experiments, they found that performance on the second observation was close to prediction While performance beyond this second observation fell considerably short of predicted values. The Ulehla et al (1968) study assumed that certainty estimations and multiple responses (i.e., a response and certainty statement following each observation) would provide optimal conditions for the effective utilization of information provided by multiple-stimulus observations. In view of the evidence given by the Swets and Birdsall (1966) and Ulehla et al(l967) experiments, it seemed logical to assume that such multiple responses and certainty estimates would serve to increase attention and vigilance.…”
mentioning
confidence: 99%